PENINGKATAN KETERAMPILAN BERPIKIR KRITIS DAN KEMANDIRIAN BELAJAR DENGAN MENGGUNAKAN MODEL PROJECT BASED LEARNING - Melyani Rizkia Putri; Ellina Rienovita; Ridha Hidayani (Edutainment : Jurnal Ilmu Pendidikan dan Kependidikan, 2025)
Amid the rapid advancement of technology and the increasing demands of the 21st century, the Project-Based Learning (PjBL) model has emerged as an innovative instructional approach that emphasizes collaboration, problem-solving, and self-directed learning in managing tasks. This study aims to analyze the improvement of students' critical thinking skills and self-directed learning in the Independent Study program at Educourse.id, which implements project-based learning. The students, who come from various academic disciplines, were involved in developing educational platforms and web-based learning tools. This study employed a quantitative method involving 119 Independent Study participants, using a questionnaire as the primary data collection instrument. The questionnaire items were constructed based on several indicators of critical thinking skills and self-directed learning. The results of the Paired Sample T-Test analysis showed a significant increase in both variables after the implementation of PjBL, with a significance value of 0.000 (p < 0.05). These findings indicate that PjBL is considered effective in enhancing students' critical thinking skills and self-directed learning.